2013
DOI: 10.4236/abc.2013.34041
|View full text |Cite
|
Sign up to set email alerts
|

Permeation of roxarsone and its metabolites increases caco-2 cell proliferation

Abstract: The benzenearsonate, Roxarsone, has been used since 1944 as an antimicrobial, growth-promoting poultry feed additive. USGS and EPA report that Roxarsone (4-hydroxy-3-nitrobenzenearsonate) and metabolites, including AHBA (3-amino-4-hydroxybenzenearsonate), contaminate waterways at greater than 1100 tons annually. To assess human impact of these organic arsenic water contaminants, it was important to study their potential absorption. The human adenocarcinoma cell line, Caco-2, is a model for intestinal absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This was consistent with the results of our previous study . Rox also increases Caco-2 cell proliferation . Besides, we found that ATP production and LD release were induced in cells exposed to Rox.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was consistent with the results of our previous study . Rox also increases Caco-2 cell proliferation . Besides, we found that ATP production and LD release were induced in cells exposed to Rox.…”
Section: Discussionsupporting
confidence: 93%
“… 15 Rox also increases Caco-2 cell proliferation. 26 Besides, we found that ATP production and LD release were induced in cells exposed to Rox. In addition, the intracellular ALD content was increased by Rox.…”
Section: Discussionmentioning
confidence: 81%